Case Report: A Pediatric Case of Familial Mediterranean Fever Concurrent With Autoimmune Hepatitis - Aoki, Mariko; Izawa, Kazushi; Tanaka, Takayuki; Honda, Yoshitaka; Shiba, Takeshi; Maeda, Yukako; Miyamoto, Takayuki; Okamoto, Keisuke; Nishitani-Isa, Masahiko; Nihira, Hiroshi; Imai, Kohsuke; Takita, Junko; et al. (Frontiers in Immunology, 2022)
Familial Mediterranean fever (FMF) is a hereditary, autoinflammatory disease that causes recurrent fever, arthritis, and serositis. The diagnosis of FMF is based on the presentation of typical clinical symptoms and the Mediterranean fever gene (MEFV) test. However, the challenge lies in diagnosing atypical cases. In this report, we have described a pediatric patient with complex FMF whose diagnosis required trio-whole exome sequencing (WES) and functional validation of a rare MEFV variant. A 3-y-old boy presented with recurrent episodes of elevated liver enzymes and arthralgia. He was diagnosed with autoimmune hepatitis (AIH), and his liver enzymes improved rapidly with steroid treatment. However, he exhibited recurrent arthralgia and severe abdominal attacks. Trio-WES identified compound heterozygous mutations in MEFV (V726A and I692del). Ex vivo functional assays of the patient’s monocytes and macrophages, which had been pre-treated with Clostridium difficile toxin A (TcdA) and colchicine, were comparable to those of typical FMF patients, thereby confirming the diagnosis of FMF. Although he was intolerant to colchicine because of liver toxicity, subsequent administration of canakinumab successfully ameliorated his abdominal attacks. However, it was ineffective against liver injury, which recurred after steroid tapering. Therefore, in this case, the pathogenesis of AIH was probably interleukin-1β (IL-1β)-independent. In fact, AIH might have been a concurrent disease with FMF, rather than being one of its complications. Nevertheless, further studies are necessary to determine whether FMF-induced inflammasome activation contributes to AIH development. Moreover, we must consider the possibility of mixed phenotypes in such atypical patients who present distinct pathologies simultaneously.